Pengaruh Proses Pengeringan Terhadap Kandungan Fitokimia Jamur Tiram Putih (Pleurotus ostreatus L.) - Azura, Nur; Parbuntari, Hesty (Departemen Kimia FMIPA UNP, 2024)
Pleurotus ostreatus or oyster mushroom is a fungi that usually consumed by people because they have a lot of nutrients and contains bioactive secondary metabolites. However, some bioactive compounds will be damaged if the sample is trough the drying process. The purpose of this study was to know the effect of the drying process on the content of bioactive compounds from oyster mushroom (Pluerotus ostreatus). The results showed a different in the content of bioactive compounds from dried and orginal Pluerotus ostreatus.. Original Pluerotus ostreatus contain bioactive secondary metabolites of alkaloids, steroids, flavonoids and saponins. While dried Pluerotus ostreatus contain alkaloids, steroids, saponin and do not contained flavonoid. Both of sample do not contained terpenoid.